Online Testing as a Means of Enhancing Students' Academic Motivation during the Coronavirus Pandemic - Stanislava Stoyanova; Vaitsa Giannouli (MDPI AG, 2022)
Although it is widely believed that online testing may be applied as a way of enhancing academic motivation, thus far we know little about this topic for Bulgarian students. For this purpose, we conducted research during the COVID-19 pandemic focusing only on university students (n = 80; 74 women, 63 full-time, 17 part-time, 41 bachelor students, 39 master's students). Participants studied online and filled in several tests online as a part of their interim control. Nine tests were created measuring knowledge and skills related to psychological measurements. Each student was provided the opportunity to respond an unlimited number of times to each test and, therefore, data were collected from 1226 testing procedures that permitted the comparison of 911 responses from full-time students with 315 responses from part-time students. Findings support the conclusion that the highest academic motivation was manifested in the best students' performance, because the students with high academic motivation had the highest test scores/attempts in online testing. The lowest academic motivation was expressed in the least efforts put into the learning process, because the students with the lowest motivation made the least number of attempts to respond to a test, compared with the students with medium and high academic motivation.